Implementation Of Environmental Awareness Character Education In Early Childhood Through Habituation (PIAUD IAIN Kudus, 2023)
The amount of waste in Indonesia continues to increase every year, which causes pollution and environmental damage. Garbage scattered everywhere will have a bad impact on living things, especially human health. This study was conducted to examine the influence of the implementation of environmental care character education through habituation on environmental care attitudes in early childhood. The method carried out in this research is a descriptive method with a case study design. The sample in the study was 3 teachers, 12 grade A students, and 6 grade B students. Data collection techniques are used by making observations, conducting interviews, and documenting activities to apply environmentally caring characteristics. The results showed that the habituation of environmental care was implemented by: 1) storing shoes and bags in lockers; 2) hand washing; and 3) disposing of garbage in its place. This habituation is supported by teachers as role models for children in applying environmental care attitudes. The implication of this study is to increase awareness of environmental care through environmental care character education in early childhood through habituation.